On the CJEU’s post-Brexit case-law on European citizenship. The recovery of the identity Ariadne’s thread? - Silveira, Alessandra (2017)
The CJEU over the years has helped to forge a concept of citizenship directed to be the “fundamental status of the nationals of the Member States”. However, since the Dereci ruling of 2011, the proactivity of the CJEU concerning the development of European citizenship seemed to have gradually exhausted itself, mostly as far as the so-called social citizenship. It happens, nonetheless, that this crucial moment the European Union faces demands the enhancement of its vertical relation with the citizenry – it is either this or fragmentation. And perhaps this is the subliminal message from the CJEU in three post-Brexit rulings that, decided in the Grand Chamber, surprisingly recover and develop the most emblematic case-law about the European citizenship – namely the Rottmann and Zambrano rulings – whose political potential and/or identity potential seemed irrevocably muzzled. The rulings Rendón Marín, CS and Petruhhin point to the connection between European citizenship and the fundamental rights protection in the EU and possibly even represent an attempt to recover the identity dimension of European citizenship, nourished by a sense of belonging to a community of rights and obligations.